Training on Videoscribe-Based HOTS Learning Media Development to Improve the Skills of Teachers - Ilma Fitriana; Fathimah Soraya; Eka Putri Surya; Alby Aruna; Abdul Rahman Prasetyo (Bubungan Tinggi: Jurnal Pengabdian Masyarakat, 2024)
The community service program in the form of training in creating HOTS-based Videoscribe learning media for Al-Azhar Islam Plus Elementary School teachers was initiated to overcome the challenges of suboptimal integration of information technology in the learning process. The distribution of teacher skills regarding technology, which is currently still low, means that many teachers in various schools still need the insight or skills to optimise the use of technology to maximise the classroom learning system. This training program aims to increase Al-Azhar Islam Plus Elementary School teachers' understanding of HOTS material for elementary school students and build teachers' skills in operating Videoscribe Sparkol software to create learning media. This training program was carried out in a structured manner using the ABCD method. During its implementation, several stages of training were carried out, namely, holding interactive workshops related to HOTS material and Videoscribe Sparkol software, group discussions, and direct practice sessions. Videoscribe, an effective learning visualisation tool, is the main focus of the training. This technology is an important means to facilitate students' HOTS development, stimulating critical, analytical and creative thinking. This training program has succeeded in increasing the understanding of Al-Azhar Islam Plus Elementary School teachers regarding HOTS material, as evidenced by the percentage of 83% of teachers who participated in the training getting a score above 80 on the post-test. The teachers at Al-Azhar Islam Plus Elementary School have also succeeded in working together and creating two learning videos using Videoscribe Sparkol software at the end of the training program. The success of this training not only confirms the need for digital literacy for teachers and highlights Videoscribe's significant potential in creating deeper and more memorable learning experiences for students, in line with the evolving needs of contemporary education. This dedication is evidence of constant efforts to perfect the teaching and learning process in the digital era, placing quality and innovation at its core.